KAJIAN REKLAMASI LAHAN PASCA TAMBANG DI JAMBI, BANGKA, DAN KALIMANTAN SELATAN - MISBAKHUL MUNIR; RR DIAH NUGRAHENI SETYOWATI (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2017)
Reclamation is an activity aimed at improving or managing the use of disturbed land as a result of mining business activities, in order to be functional and efficient according to its allocation. Mining reclamation activities should be carefully planned so that the land can be utilized optimally by the government and communities around the mine. Reclamation in Indonesia has been done in several mining areas. Reclamation activities that have been carried out, among others, exist in three regions in Indonesia, namely in Jambi, Bangka and South Kalimantan are considered less effective, due to lack of public participation and errors of reclamation technology. To avoid obstacles from reclamation, an effective reclamation activity is required. In general, reclamation can be done in three stages: land preparation, planting and maintenance.